2018
DOI: 10.1007/s10549-018-4879-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tumor molecular heterogeneity in breast cancer: definitions of measures and association with distant recurrence-free survival

Abstract: Intra-tumor heterogeneity of ER receptor status may be a predictor of patient DRFS. Histopathologic data from multiple tissue samples may offer a view of tumor heterogeneity and assess recurrence risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The resulting cell embeddings (first 30 components, henceforth referred to as ‘PCA space’) were finally used to construct the Shared Nearest-Neighbors (SNN) graph (constructed from an initial k-NN search with k=30, as implemented in the buildSNNGraph() function from scran) that fed Louvain clustering (implemented in the cluster_louvain() function from igraph [74]. We chose the clustering solution upon inspection of other possible clustering solutions, each obtained from the Louvain partitioning of different SNN graphs (each constructed from different initial k-NN searches, with k in [5,10,15,20,30,50]. For each clustering solution, we evaluated: i) clusters compactness and separation, with the Davies-Boudain (DB) index [75].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting cell embeddings (first 30 components, henceforth referred to as ‘PCA space’) were finally used to construct the Shared Nearest-Neighbors (SNN) graph (constructed from an initial k-NN search with k=30, as implemented in the buildSNNGraph() function from scran) that fed Louvain clustering (implemented in the cluster_louvain() function from igraph [74]. We chose the clustering solution upon inspection of other possible clustering solutions, each obtained from the Louvain partitioning of different SNN graphs (each constructed from different initial k-NN searches, with k in [5,10,15,20,30,50]. For each clustering solution, we evaluated: i) clusters compactness and separation, with the Davies-Boudain (DB) index [75].…”
Section: Methodsmentioning
confidence: 99%
“…Seminal work showed that the potential of metastasis spreading in BC significantly correlates with the degree of genetic and/or phenotypic heterogeneity in the PT [9], [10], [11]. Early studies hypothesized that specific mutations in primary breast tumors are selected by the metastatic phenotype [12].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer has been seriously endangering the public health because of its high incidence in women [ 1 , 2 ]. According to the expression of molecular markers (estrogen receptor, progesterone receptor, and HER2), breast cancer can be divided into several subtypes: luminal A, luminal B, HER2+, and triple-negative [ 3 ]. According to the different subtypes, there are different therapeutic strategies in clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, another study quantifying the genetic intra-tumor diversity in patient-specific mutational profiles of more than 900 TCGA (The Cancer Genome Atlas) BC patients showed an inverse correlation between ITH and overall survival [ 152 , 153 ]. Moreover, the analysis of estrogen receptor expression across 970 different breast tumors revealed that patients with the most heterogeneous expression display an increased risk of distant metastases [ 154 ]. Thus, the co-existence of heterogeneous populations of cells within the same PT favors distant metastases, suggesting that different clones may develop cooperative interactions [ 155 , 156 ].…”
Section: Bc Intra-tumor Heterogeneity and Metastasismentioning
confidence: 99%